How Global Languages Spread in Africa? A Geographic Insight from International Language Promotion Institutions - Du, M.; Li, L.; Li, G.; Nie, Q.; Wang, Y.; Huang, Y.; Niu, X. (Department of Geography, University of Colombo, 2023)
Language promotion institutions are important platforms for countries to promote language and cultural exchanges. Taking the typical international language promotion institutions established in Africa as the research objects, this paper explores their spatio-temporal evolution and formation mechanism from a geographical perspective. The methods used in this research are mathematical statistics and spatial analysis and the results show that: The temporal pattern of international language promotion institutions in Africa can be divided into three stages; namely "slow growth - ups and downs - rapid growth." The spatial pattern shows that international language promotion institutions are present in most African countries. In the development, they have shown a trend of coastal distribution, and are mainly concentrated on the southern coast of Central Africa and the eastern coast of the whole continent. There are three distribution preferences in Africa for typical international language promotion institutions from different countries: Scattered distribution in a few countries, concentrated distribution in coastal areas, and proximity to promotion countries. The regression results show that GDP, import of cultural goods, historical international language promotion institutions of a country, and the bilateral trade volume affect the development of international language promotion institutions in Africa. This paper argues that the spatio-temporal pattern of international language promotion institutions in Africa has been formed under the push of the promotion country and the pull of the host country.
Keywords: International language promotion institutions; spatio-temporal evolution; influencing mechanism; Africa